Limitations of Spinal Anesthesia for Patient and Surgeon During Percutaneous Nephrolithotomy - Basiri, Abbas; Kashi, Amir Hossein; Zeinali, Mahdi; Nasiri, Mahmoud Reza; Valipour, Reza; Sarhangnejad, Reza (Urology Journal, 2018)
Purpose: To evaluate the intraoperative pain score of patients who undergo percutaneous nephrolithotomy under spinal anesthesia and to evaluate surgeons' and patients' convenience with this type of anesthesia. Materials and Methods: PCNL cases who were performed by two endourology fellows under spinal anesthesia during June to July 2014 were included. Spinal anesthesia was performed using injection of 0.25mg/kg bupivacaine 0.5% in the intrathecal space. All procedures were performed with the patient in the prone position. Stone access was made by using ?uoroscopic guidance, and the tract was dilated using a single-stage technique. Visual analogue pain score was used to assess patients' pain during operation, immediately after, and 2 hours later. Results: 50 patients were enrolled during the study period. Visual analogue pain score of 10 and 8 were observed in 5 and three patients respectively. In two patients the operation was terminated because of patient anxiety and pain. In another patient a second access was not obtained to remove a staghorn stone because of patient's agitation. Gross agitation was observed in six patients. Apart from flank pain, intraoperative pain was felt in the flank, scapula, abdomen and/or chest. Conclusion: Spinal anesthesia does not provide enough analgesia for the patient in a limited frequency of percutaneous nephrolithotomy operations. We could not find statistically significant predictors of insufficient analgesia based on patients' demographics, stone characteristics or access location.